Peran Kantor Pertanahan Kota Tanjungbalai dalam Pelaksanaan Pendaftaran Tanah Sistematis Lengkap di Kota Tanjungbalai - Hasyanul Arief Sinaga; Dayat Limbong; Isnaini Isnaini (Mahesa Research Center, 2022)
This article aims to analyze the role of the Tanjungbalai City Land Office to reduce and prevent disputes/conflicts and what factors are obstacles in reducing and preventing disputes/conflicts. This type of research is normative legal research. The approach method used is the statute approach. Based on the research, the legal regulation regarding PTSL in Indonesia is Permen ATR/Head of BPN Number 6 of 2018 concerning PTSL contained in Presidential Instruction No. 2 of 2018 concerning Acceleration of PTSL throughout the Republic of Indonesia. The role of the Tanjungbalai City Land Office to reduce and prevent disputes/conflicts is as a mediator in land disputes that occur, carrying out studies and handling problems, disputes, land cases, through non-litigation methods: first, the Land Office takes a persuasive approach to the community, seeking information related disputes. Second, outreach to the community regarding this dispute. Third, deliberation is carried out with the disputing parties with community leaders. Then the object of the dispute is merged and land registration is carried out through PTSL. After the certificate is issued, the Land Office distributes the land parcels to the entitled parties. Factors that become obstacles in reducing and preventing disputes/conflicts, namely: a) it is difficult to contact the disputing parties, b) the disputing parties do not want to budge, c) socialization and mediation are difficult, d) it is difficult to find common ground between the parties. in dispute, e) takes a long time.